Single-Electron Charging Effects in Hybrid Organic/Inorganic Nanomembrane-Based Junctions - De Oliveira, Rafael Furlan; Merces, Leandro; Marques, Felipe; Teixeira-Neto, Érico; De Camargo, Davi Henrique Starnini [UNESP]; Bufon, Carlos César Bof (American Chemical Society (ACS), 2018)
The controllable transfer of a single electron in devices (SEDs) is one of the viable trends for a new generation of technology. However, novel applications demand innovative strategies to fabricate and evaluate SEDs. Here, we report a hybrid organic/inorganic SED that combines an ensemble of physisorbed, semiconducting molecular layers (SMLs) and Au nanoclusters embedded in the transport channel by in situ, field-induced metal migration. The SED is fabricated using an integrative platform based on rolled-up nanomembranes (rNMs) to connect ultrathin SMLs from the top, forming large-area tunnel junctions. The combination of high electric fields (1-4 MV/cm), electrode point contacts, low temperatures (10 K), and ultrathin molecular layers (<10 nm) lead to field-induced migration of Au electrode nanoparticles inward the SML of the junction channel. This phenomenon can be either observed in the as-prepared rNM junctions or intentionally induced by the application of high electric fields (>1 MV/cm). The propelled electrode particles become trapped in the soft molecular material, acting as Coulomb islands positioned in between a double-barrier tunnel junction. As a result, the hybrid organic/inorganic rNM junctions present single-charge effects, namely Coulomb blockade and Coulomb staircase. Such an in situ, field-induced metal migration process opens possibilities to create novel and complex SEDs by using different molecular materials. From another perspective, the reported metal diffusion in such nanoscale junctions deserves attention as it can occasionally mask molecule-dependent responses.